An IoT based efficient water management system for smart irrigation to enhance the maize crop productivity - Prema, P; Veeramani, A; Sivasankari, B; Sujatha, P; Illamaran, M; Shanmugapriya, S P (Plant Science Today, 2025)
Agriculture contributes a major share to the Indian economy and most of its people are dependent on it for their livelihood. This makes water an important resource that must be preserved using the latest available technologies. An adequate amount of water for irrigation is needed for healthy crops and to increase productivity. Water scarcity is a major problem facing the world, where agriculture consumes a significant portion of freshwater. Many researchers have focused on developing intelligent irrigation systems using Internet of Things (IoT) technology. This paper presents an IoT-based, cost-effective intelligent water management system for smart irrigation. The developed system uses soil moisture and weather data to take intelligent decisions to automate irrigation using a cloud-, web- and mobile-based applications. The proposed system uses eight treatments with four types of irrigation methods such as IoT-based drip irrigation (60 % and 80 % depletion levels - T1 and T2); drip irrigation based on PE ratio (60 % and 80 % depletion levels - T3, T4 and normal practice T5); surface irrigation based on IW/CPE ratio (60 % and 80 % depletion levels - T6, T7) and flood irrigation (T8) are used. In all systems, water was applied at 60 % and 80 % depletion levels. This demonstrates the IoT- and cloud-based system enable precision agriculture by reducing human intervention in irrigation. The highest water saving was recorded in IoT-based drip irrigation at 60 % depletion level (46.88 %), followed by IoT-based drip irrigation at 80 % depletion level (40.63 %). Therefore, the proposed IoT-based drip irrigation system at 60 % depletion level can be recommended for hybrid maize to achieve higher grain and straw yields.